2020
DOI: 10.1016/j.ijid.2020.09.014
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19: Poor outcomes in patients with zinc deficiency

Abstract: Background: Zinc is a trace element with potent immunoregulatory and antiviral properties, and is utilized in the treatment of coronavirus disease 2019 (COVID-19). However, we do not know the clinical significance of serum Zinc levels in COVID-19 patients. The aim of this study was to determine the clinical significance of serum zinc in COVID-19 patients and to establish a correlation with disease severity. Methods: This was a prospective study of fasting zinc levels in COVID-19 patients at the time of hospita… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

13
228
1
11

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 245 publications
(275 citation statements)
references
References 29 publications
13
228
1
11
Order By: Relevance
“…Indeed, there is some scientific evidence on immune-boosting, anti-inflammatory, antioxidant, and antiviral properties of several bioactive compounds and foods, including vitamins D and C, zinc, selenium, garlic, ginger, turmeric, lactoferrin, elderberry, or Nigella sativa , however they cannot be freely extrapolated to the effects on the SARS-CoV-2 virus [ 9 , 11 , 14 , 22 , 23 , 34 ]. Recently, the compounds like vitamin D, vitamin C, zinc, probiotics, curcumin, quercetin have been extensively studied in the context of coronavirus [ 34 , 35 , 36 ]. Initial surveys have found them to possess an anti-SARS-CoV-2 effect, and suggest they might provide both prophylactic and adjuvant therapy against COVID-19 effects, therefore, they are being fast-tracked into clinical trials [ 34 , 35 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Indeed, there is some scientific evidence on immune-boosting, anti-inflammatory, antioxidant, and antiviral properties of several bioactive compounds and foods, including vitamins D and C, zinc, selenium, garlic, ginger, turmeric, lactoferrin, elderberry, or Nigella sativa , however they cannot be freely extrapolated to the effects on the SARS-CoV-2 virus [ 9 , 11 , 14 , 22 , 23 , 34 ]. Recently, the compounds like vitamin D, vitamin C, zinc, probiotics, curcumin, quercetin have been extensively studied in the context of coronavirus [ 34 , 35 , 36 ]. Initial surveys have found them to possess an anti-SARS-CoV-2 effect, and suggest they might provide both prophylactic and adjuvant therapy against COVID-19 effects, therefore, they are being fast-tracked into clinical trials [ 34 , 35 ].…”
Section: Discussionmentioning
confidence: 99%
“…Recently, the compounds like vitamin D, vitamin C, zinc, probiotics, curcumin, quercetin have been extensively studied in the context of coronavirus [ 34 , 35 , 36 ]. Initial surveys have found them to possess an anti-SARS-CoV-2 effect, and suggest they might provide both prophylactic and adjuvant therapy against COVID-19 effects, therefore, they are being fast-tracked into clinical trials [ 34 , 35 ]. Recent studies have linked deficiency of zinc [ 35 ], selenium [ 37 ], or vitamin C [ 36 , 38 ] to poorer COVID-19 outcomes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There has been one case study report describing beneficial effects of zinc supplementation for COVID-19 progression [ 157 ], and more recently, the first in vivo evidence of zinc supplementation for better COVID-19 outcomes [ 158 ]. It has also been reported that COVID-19 patients had significantly lower zinc levels compared with healthy individuals, and this was associated with a greater than 5-fold increased likelihood of developing complications [ 159 ]. Since supplementation strategies will be different for preexisting zinc deficiency versus a deficiency acquired during SARS-CoV-2 infection, with acute deficiency during viral infection requiring active monitoring and interventions, it is important to distinguish these cases and their combination.…”
Section: Introductionmentioning
confidence: 99%
“…Zinc has been shown to mediate antiviral effects through improving the mucociliary clearance of virus, strengthening the integrity of the epithelium, decreasing viral replication, preserving antiviral immunity, attenuating the risk of hyperinflammation, supporting anti-oxidative effects (11). Observational studies have reported that lower baseline zinc levels in hospitalized adults were associated with a higher risk of mortality, complications, and longer hospital stay following SARS-CoV-2 infection (12), suggesting potential benefits of zinc supplementation in reducing COVID-19 morbidity and mortality. Moreover, the clinical trials on zinc supplementation in combination with other drugs such as hydroxychloroquine or chloroquine have been registered (13), and the anticipated results coming soon.…”
Section: Introductionmentioning
confidence: 99%